FEATURES OF INFORMATION TECHNOLOGY MANAGEMENT IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2024)
This article examines the place and role of management information systems in the activities of enterprises and organizations in the Republic of Uzbekistan. It highlights that, alongside traditional information systems, specialized management information systems have been developed and are functioning effectively within the national economy. These systems contribute to efficient information processing and the adoption of sound managerial decisions.